Causes of Changes in Mineralization of Underground Drinking Water in the Shaim Oil and Gas Region of the West Siberian Megabasin - Yulia Rusakova; Andrey Plavnik; Rimma Abdrashitova; Yulia Salnikova; Xiaopu Wang; Mikhail Poluyanov; Albert Zaliatdinov (Earth)
Mineralization of groundwater for drinking purposes is a complex parameter of groundwater chemical composition. In the Shaim oil- and gas-bearing area, as in the whole West Siberian megabasin, the main target horizon for solving the issues of domestic and technical water supply is the Oligocene aquifer. It has significant groundwater reserves to cover the needs of the population and production requirements. However, it also faces a huge anthropogenic load in the form of water withdrawal and possible contamination from the surface with oil products. In Western Siberia, various deviations in the chemical composition of groundwater of the Oligocene horizon are recorded in connection with significant water withdrawal; for example, a sharp increase in chromaticity or total iron concentration, with changes in mineralization acting as a factor necessarily accompanying these deviations. Based on the data obtained in the course of monitoring for the period from 2013 to 2023, the main factors and trends of changes in the components of mineralization of the Oligocene horizon were determined. The lithological and mineralogical peculiarities of the water-bearing rocks of the horizon, the paleogeographic conditions of its formation and their relation to trends in mineralization change were studied. Water withdrawal data were processed for two cluster water withdrawal sites (50 and 5 wells, respectively). Analysis of the results showed that the increase in water withdrawal leads to an increase in infiltration from the overlying Neogene-Quaternary aquifer, which leads to the dilution of groundwater of the Oligocene horizon and a decrease in its mineralization. Here, we show that, during further monitoring, it is necessary to pay attention to the appearance of sites where significant amounts of chloride ions are fixed in the anion composition, which can potentially lead to a sharp deterioration in the quality of drinking groundwater.